Graphic humour: approaches of COVID-19 in Ecuadorian newspaper El Universo - Bravo Mancero, Julio Adolfo (2020)
This paper investigates the coverage used by cartoonist Bonil, in ecuadorian newspaper El Universo, to represent the advance of pandemic COVID-19. Mixed methodology was used: qualitative and quantitative,through the documentary review, content analysis and discourse analysis, to 25 cartoons, published between March 13 and April 10, 2020. The results showed contents were disseminated into the following axes: Health, Economy, Politics, Corruption, Society and Technology. Iconic and verbal elements, through the construction of visual metaphors, served to warn public opinion of pandemic consequences as well as to watch spaces of power, domination and inequality, highlighted Ecuadorian society weakness.